1993
DOI: 10.1159/000204363
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Characteristics of Colony-Forming Unit-Erythroid Colonies in Myelodysplastic Syndrome Patients

Abstract: The microcytofluorometrical method was applied to determine the relative hemoglobin (Hb) content in the bone marrow colony-forming unit-erythroid (CFU-E) colonies from 6 patients with myelodysplastic syndromes (MDS) and 10 healthy subjects. This method relies on a photochemical reaction, by which intracellular Hb is converted into fluorescent porphyrin using a 0.2 M mercaptoethylamine solution (an SH donor) and violet light (λ = 405 nm). The relative Hb content was determined as a function of the intensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Several in vitro studies have shown that erythroid progenitors in vitro do not expand in response to epo or epo plus MGF stimulation. [2][3][4][5][6][7][8] Also the in vivo treatment of MDS patients with rhEPO is of limited benefit. [25][26][27] However, in spite of the limited in vitro proliferative capacity of the erythroid progenitor cell, a normal or increased number of normoblasts are observed in the bone marrow suggesting that in vivo the differentiation pathway is not totally blocked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies have shown that erythroid progenitors in vitro do not expand in response to epo or epo plus MGF stimulation. [2][3][4][5][6][7][8] Also the in vivo treatment of MDS patients with rhEPO is of limited benefit. [25][26][27] However, in spite of the limited in vitro proliferative capacity of the erythroid progenitor cell, a normal or increased number of normoblasts are observed in the bone marrow suggesting that in vivo the differentiation pathway is not totally blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have shown that BFU-E and CFU-E do not expand in response to erythropoietin (Epo) or Epo plus mast cell growth factor (MGF). [2][3][4][5][6][7][8] Moreover a differentiation block is observed at the level of early erythroid progenitor cell which is frequently associated with the aberrant expression of Evi-1. 9 The Evi-1 gene encodes a zinc finger protein that functions as transcription factor.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the values of the nucleolar coefficient express the average number of nucleoli per cell (9), and thus some proerythroblasts in R A patients may contain a similar number of nucleoli as in controls. The coexistence of normal and abnormal erythropoiesis in R A of MDS is already known from previous studies based on different methodical approaches (17). Unfortunately, in the present study the limited number of proerythroblasts in investigated specimens did not permit the classification of these cells based on the incidence and number of nucleoli, and thus a more precise cytological study in this direction was not possible.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, it should be mentioned that some erythroblasts in advanced stages of maturation in RA patients still contained micronucleoli the presence of which was characteristic of patients without disturbed erythropoiesis. Note that the coexistence of normal and abnormal cell clones, including erythroid cells in RAs of MDS, is generally known (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Στην παρούσα διατριβή πραγματοποιήσαμε βραχείας διάρκειας καλλιέργειες από ασθενείς όλων των κατηγοριών κατά FAB με την χρήση, του κλασσικού και του εμπλουτισμένου υλικού, ώστε να συγκρίνουμε την ανάπτυξη των αποικιών και να τη συσχετίσουμε με την κλινική ανταπόκριση των ιδίων ασθενών στον συνδυασμό Epo και G-CSF. Η ανάπτυξη in vitro των αποικιών BFU-E έχει συσχετισθεί θετικά με τα επίπεδα αιμοσφαιρίνης, ενώ η ανάπτυξη μεγακαρυοκυτταρικών αποικιών με τον αριθμό των αιμοπεταλίων (Maruo N et al 1993, Depaoli L et al 1993Geissler D et al 1989. Εν τούτοις η ανάπτυξη των αποικιών in vitro έχει βρεθεί ότι δεν εξαρτάται από το Bournemouth score, την ύπαρξη καρυοτυπικών ανωμαλιών και την έκφραση CD95 και κασπάσης-3.…”
Section: βραχείας διάρκειας καλλιέργειεςunclassified